2017
DOI: 10.3748/wjg.v23.i23.4158
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriBabA in adaptation for gastric colonization

Abstract: Helicobacter pylori (H. pylori) as a causative agent of gastric complications, is well adapted for the colonization of gastric mucosa. Although the infectious process depends on several factors, the adhesion to the gastric mucosa is the first and important step. Among several outer membrane proteins, BabA is one of the significant protein involving in many inflammatory processes in addition to its role in the attachment for the persistent colonization. We performed a PubMed search using the key words: “babA”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 95 publications
2
67
0
15
Order By: Relevance
“…Indeed, the cagA/vacAs1m1 genotype was found in 20.6% isolates from patients of mild-vs 54.5% from severe-disease group, which agrees with the association between this genotype and the higher pathogenicity. 11 Prevalence of babA2 varies widely among different populations; from 35%-60% in Europe to 100% in Asia, 11,31 most of our isolates were positive for babA2 (>94%) but we could not know if the protein was expressed or not, further studies should be done in order to know if posttranscriptional modification occurred. 30 Infection experiments showed that 22.2% cagA-positive strains were unable to translocate CagA into the host cells, showing non-expression of cagA or a non-functionality of the cag-T4SS of these strains.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Indeed, the cagA/vacAs1m1 genotype was found in 20.6% isolates from patients of mild-vs 54.5% from severe-disease group, which agrees with the association between this genotype and the higher pathogenicity. 11 Prevalence of babA2 varies widely among different populations; from 35%-60% in Europe to 100% in Asia, 11,31 most of our isolates were positive for babA2 (>94%) but we could not know if the protein was expressed or not, further studies should be done in order to know if posttranscriptional modification occurred. 30 Infection experiments showed that 22.2% cagA-positive strains were unable to translocate CagA into the host cells, showing non-expression of cagA or a non-functionality of the cag-T4SS of these strains.…”
Section: Discussionmentioning
confidence: 79%
“…Antibiotic susceptibility testing should be performed prior to therapy and regional surveillance of primary antibiotic resistance of H pylori is recommended. 11,12 The functional status of OipA is regulated by slipped-strand mispairing that is determined by the number of CT dinucleotide repeats in the 5´region of the gene (status ON is functional and OFF is nonfunctional). Several factors contribute to this situation such as environmental parameters, host genetic susceptibility and bacteria virulence factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through co-evolution, chronic pathogens with vertical or familial transmission become less virulent over time [8993], and H. pylori infections are well tolerated by humans, causing low-grade inflammation and possibly protecting against allergic and related disorders [2529, 94, 95]. The H. pylori gene babA2 demonstrates adaptive microevolution with humans [96]. BabA binds blood group antigens and triggers pro-inflammatory cytokine release.…”
Section: Human Factors: Germline and Somaticmentioning
confidence: 99%